A Systematic Review and Narrative Synthesis of Interventions for Parental Human Immunodeficiency Virus Disclosure - Conserve, Donaldson F.; Teti, Michelle; Shin, Grace; Iwelunmor, Juliet; Handler, Lara; Maman, Suzanne (Frontiers in Public Health, 2017)
Introduction: Disclosure of parental HIV infection to their children remains a difficult process for parents living with HIV (PLWH). In order to identify the best strategies to facilitate parental HIV disclosure, it is necessary to examine the efficacy of existing interventions designed to help PLWH parents with the disclosure process to their children. Objectives: To systematically review the efficacy of interventions designed to assist PLWH disclose their HIV status to their children. Methods: We conducted a systematic review and narrative synthesis of interventions designed to assist PLWH disclose their HIV status to their children. MEDLINE/PubMed, PsycINFO, Embase, Global Health, and Web of Science were searched. Results: Studies were eligible for inclusion if they evaluated an intervention for parental HIV disclosure. Five studies published between 2001 and 2015 met the inclusion criteria. The interventions were conducted in South Africa, China, and the United States. Three of the studies used two-arm randomized controlled trials (RCTs), in which the intervention group was given enhanced care while the control group received standard care. Four of the 5 studies included a theoretically informed intervention and three were limited to mothers. Results showed that four of the interventions increased parental HIV disclosure. Conclusion: The findings suggest that parental HIV disclosure interventions are successful in assisting parents with the disclosure process and can be adapted in different cultural context. Future parental HIV disclosure interventions should include fathers in order to assist men with parental HIV disclosure.